2000
DOI: 10.1074/jbc.m005465200
|View full text |Cite
|
Sign up to set email alerts
|

A Binding Site for the Kringle II Domain of Prothrombin in the Apple 1 Domain of Factor XI

Abstract: Previously we defined binding sites for high molecular weight kininogen (HK) and thrombin in the Apple 1 (A1) domain of factor XI (FXI). Since prothrombin (and Ca(2+)) can bind FXI and can substitute for HK (and Zn(2+)) as a cofactor for FXI binding to platelets, we have attempted to identify a prothrombin-binding site in FXI. The recombinant A1 domain (rA1, Glu(1)-Ser(90)) inhibited the saturable, specific and reversible binding of prothrombin to FXI, whereas neither the rA2 domain (Ser(90)-Ala(181)), rA3 dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…Meanwhile, the chi-squared value of TK peptide was calculated to be 7.01 by Biacore 3000 Evaluation Software version 4.5, which demonstrated a good fit. This was in accordance with the finding of Baglia et al (2000) who chi-square values less than 10 indicate a good fit. These findings indicated that TK had a high binding affinity to integrin a 6 b 1 .…”
Section: Molecular Binding Affinitysupporting
confidence: 92%
“…Meanwhile, the chi-squared value of TK peptide was calculated to be 7.01 by Biacore 3000 Evaluation Software version 4.5, which demonstrated a good fit. This was in accordance with the finding of Baglia et al (2000) who chi-square values less than 10 indicate a good fit. These findings indicated that TK had a high binding affinity to integrin a 6 b 1 .…”
Section: Molecular Binding Affinitysupporting
confidence: 92%
“…Regarding missense mutations, Gly79Ala occurs in the C-terminal portion of the Ap1 domain, which contains the binding sites for HK, thrombin, and prothrombin [20]. Although the structural change predicted by a Gly-to-Ala substitution is subtle, inspection of the 3D structure of the protein region surrounding Gly79 shows that this residue is part of a b-strand forming a three-stranded antiparallel b sheet.…”
Section: Discussionmentioning
confidence: 99%
“…Most frequently, however, PAN domains are present in tandem arrays (46). For example, clotting factor XI consists of a serine protease domain fused to four tandem apple domains, each domain with a specific ligand-binding function (49)(50)(51). Similarly, T. gondii MIC-4 apple domains have distinct functions.…”
Section: Ama1 Domains I؉ii Consists Of Two Tandem Pan Domainsmentioning
confidence: 99%